2015
DOI: 10.1039/c5ee01215e
|View full text |Cite
|
Sign up to set email alerts
|

Lithium salts for advanced lithium batteries: Li–metal, Li–O2, and Li–S

Abstract: Presently lithium hexafluorophosphate (LiPF 6 ) is the dominant Li-salt used in commercial rechargeable lithium-ion batteries (LIBs) based on a graphite anode and a 3-4 V cathode material. While LiPF 6 is not the ideal Li-salt for every important electrolyte property, it has a uniquely suitable combination of properties (temperature range, passivation, conductivity, etc.) rendering it the overall best Li-salt for LIBs. However, this may not necessarily be true for other types of Li-based batteries. Indeed, nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
389
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 500 publications
(394 citation statements)
references
References 186 publications
(363 reference statements)
4
389
0
1
Order By: Relevance
“…than the FSIbased analogs. 20 These values illustrate the crucial effect of the size and shape of the cation in combination with the size and shape of the anion on the packing and crystallization behavior of the salt. 21 It was also observed that P 1113 FSI was the only ionic liquid that showed extra peaks below melting that can be attributed to the presence of other phases/crystalline structures of lower melting points or due to a solid-solid transition corresponding to a regular crystalline to plastic crystalline phase.…”
Section: Resultsmentioning
confidence: 99%
“…than the FSIbased analogs. 20 These values illustrate the crucial effect of the size and shape of the cation in combination with the size and shape of the anion on the packing and crystallization behavior of the salt. 21 It was also observed that P 1113 FSI was the only ionic liquid that showed extra peaks below melting that can be attributed to the presence of other phases/crystalline structures of lower melting points or due to a solid-solid transition corresponding to a regular crystalline to plastic crystalline phase.…”
Section: Resultsmentioning
confidence: 99%
“…Li-metal has higher energy density compared to other negative electrodes, but it suffers from dendrite formation, low cycling Coulombic efficiency, etc. 5 In this work, we study how the electrochemical performance of NMC cathodes is influenced by the choice of negative electrode, and how the surface layer formed on NMC positive electrode depend on the negative electrode material, by investigations of NMCLi-metal, NMC-LTO and NMC-graphite cells. This is motivated by the extensive use of Li-metal in literature to bench-mark cathode materials, which can neglect the influence of the negative elecz E-mail: reza.younesi@kemi.uu.se trode itself on the potential profile and cycling life of the positive electrode.…”
mentioning
confidence: 99%
“…These results were obtained by measuring non-destructively a commercial lithium-ion battery. Recently, the use of lithium metal as a negative electrode material has been considered to result in high-performance batteries, as the lithium metal has the highest theoretical capacity, 3861 mAh/g, among general negative electrode materials [13][14][15]. However, there is a problem that lithium dendrite occurs at the surface of the negative electrode.…”
Section: Resultsmentioning
confidence: 97%